The history of Reynard the Fox : his friends and his enemies, his crimes, hairbreadth escapes and final triumph : a metrical version of the old English translation with glossarial notes in verse - Ellis, F.S.; Crane, Walter (London : David Nutt Chiswick Press, 1897)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: Reinaert de vos; legenden; folklore